HUBUNGAN PENDAPATAN TERHADAP POLA MAKAN TUKANG KEBUN DI UNIVERSITAS NEGERI MEDAN - Yusfa Hanum; Olga Utami Siregar (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT This study aims to determine the relationship of income with diet of  gardeners at State University of Medan. The population  of this  study were all gardeners Medan State University who were 30 and drawn samples with total sampling number of 30 people consisting of 17 men - men and 13 women with with age 55-61 years.Data of the research were collected by distributing questionnaires to the income variable (X) and variable diet gardener (Y) by way of "recal" 2 x 24 hour back by asking respondents  about the food consumed in a day (breakfast, lunch and dinner) plus a snack. from the description of the data obtained trend level income variable (X) tends to the low and variable levels of dietary gardener (Y) of degree less food consumption category. results of the second test requirements analysis found normally distributed variables and the regression equation Y = 22.142 + 96.116 X is a linear  indicating a positive relationship between income and linear with diet gardeners Medan. data analysis techniques used is the statistical analysis of the product moment correlation Karl Pearson.result of  correlation analysis showed a relationship with a earnings diet gardener  in Medan State university, with a correlation coefficient r xy of 0.576 at significant level of 5% (count r> r table: 0.576> 0.36) the hypothesis is accepted that means that the lower the income  the lower the diet is. Kata Kunci : Pendapatan, pola makan.